2004
DOI: 10.1007/s00497-003-0200-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structural features of the S haplotype-specific F-box protein, SFB, in Prunus

Abstract: The gene SFB encodes an F-box protein that has appropriate S-haplotype-specific variation to be the pollen determinant in the S-RNase-based gametophytic self-incompatibility (GSI) reaction in Prunus (Rosaceae). To further characterize Prunus SFB, we cloned and sequenced four additional alleles from sweet cherry (P. avium), SFB 1 , SFB 2 , SFB 4 , and SFB 5 . These four alleles showed haplotype-specific sequence diversity similar to the other nine SFB alleles that have been cloned. In an amino acid alignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 38 publications
10
130
1
2
Order By: Relevance
“…Conserved nucleotides are shown on a darkened background. The locations of the F-box motif-V1, V2, HVa and HVb (Ikeda et al 2004a), and Vn (Nunes et al 2006)-are indicated by solid boxes. The asterisks under the amino acid sequence indicate the five amino acid residues that differ between SFB 36a and SFB 36b .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conserved nucleotides are shown on a darkened background. The locations of the F-box motif-V1, V2, HVa and HVb (Ikeda et al 2004a), and Vn (Nunes et al 2006)-are indicated by solid boxes. The asterisks under the amino acid sequence indicate the five amino acid residues that differ between SFB 36a and SFB 36b .…”
Section: Resultsmentioning
confidence: 99%
“…These fosmid libraries were screened at 60°with a mixture of DIGdUTP-labeled S 6 -RNase and SFB 6 probes, as previously described (Ushijima et al 2001). The DIG-labeled S 6 -RNase and SFB 6 probes were obtained by PCR labeling using a PCR DIG probe synthesis kit (Roche) with Pru-C2 and PCE-R primers (Tao et al 1999;Yamane et al 2001) and SFB-C1F (Ikeda et al 2004a) and SFB-C4R primers (Yamane et al 2003c), respectively. The S haplotype of each positive fosmid clone was determined by PCR with the S-RNase consensus primer pair (Pru-C2 and PCE-R), which detects length differences for the second intron of the S-RNase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on amino acid sequence comparison, Ikeda et al (2004) first summarized the structural features for Prunus SFB alleles. In this study, the structures of the 5 new SFB alleles were similar to other Prunus SFB alleles.…”
Section: Sequence Analysis and Comparison Of Sfb Alleles Identified Imentioning
confidence: 99%
“…After the first identification of S-RNase in the Solanaceae (McClure et al, 1989), a very good candidate gene for the pollen S gene, an SFB, was recently found in several species of Prunus in the Rosaceae, including sweet cherry (P. avium; Yamane et al, 2003a;Ikeda et al, 2004;Sonneveld et al, 2005;Vaughan et al, 2006), almond (P. dulcis; Ushijima et al, 2003Ushijima et al, , 2004Sutherland et al, 2008), Japanese apricot (P. mume; Entani et al, 2003;Yamane et al, 2003b), apricot (P. armeniaca; Romero et al, 2004;Vilanova et al, 2006;Wu et al, 2009), Japanese plum (P. salicina; Zhang et al, 2007), dwarf almond (P. tenella; Šurbanovski et al, 2007), and Chinese cherry (P. pseudocerasus; Huang et al, 2008;Gu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%